2021 Otto Aufranc Award: A simple Hip-Spine Classification for total hip arthroplasty: validation and a large multicentre series. (1st July 2021) - Vigdorchik, Jonathan M.; Sharma, Abhinav K.; Buckland, Aaron J.; Elbuluk, Ameer M.; Eftekhary, Nima; Mayman, David J.; Carroll, Kaitlin M.; Jerabek, Seth A.
Abstract : Aims: Patients with spinal pathology who undergo total hip arthroplasty (THA) have an increased risk of dislocation and revision. The aim of this study was to determine if the use of the Hip-Spine Classification system in these patients would result in a decreased rate of postoperative dislocation in patients with spinal pathology. Methods: This prospective, multicentre study evaluated 3, 777 consecutive patients undergoing THA by three surgeons, between January 2014 and December 2019. They were categorized using The Hip-Spine Classification system: group 1 with normal spinal alignment; group 2 with a flatback deformity, group 2A with normal spinal mobility, and group 2B with a stiff spine. Flatback deformity was defined by a pelvic incidence minus lumbar lordosis of > 10°, and spinal stiffness was defined by < 10° change in sacral slope from standing to seated. Each category determined a patient-specific component positioning. Survivorship free of dislocation was recorded and spinopelvic measurements were compared for reliability using intraclass correlation coefficient. Results: A total of 2, 081 patients met the inclusion criteria. There were 987 group 1A, 232 group 1B, 715 group 2A, and 147 group 2B patients. A total of 70 patients had a lumbar fusion, most had L4-5 (16; 23%) or L4-S1 (12; 17%) fusions; 51 patients (73%) had one or two levels fused, and 19 (27%) had > three levels fused. Dual mobility (DM) components were used in 166 patients (8%), including all of those in group 2B and with > three level fusions. Survivorship free of dislocation at five years was 99.2% with a 0.8% dislocation rate. The correlation coefficient was 0.83 (95% confidence interval 0.89 to 0.91). Conclusion: This is the largest series in the literature evaluating the relationship between hip-spine pathology and dislocation after THA, and guiding appropriate treatment. The Hip-Spine Classification system allows surgeons to make appropriate evaluations preoperatively, and it guides the use of DM components in patients with spinopelvic pathology in order to reduce the risk of dislocation in these high-risk patients. Cite this article: Bone Joint J  2021;103-B(7 Supple B):17–24.